Together we are strong? A systematic literature review on how SMEs use relation-based collaboration to operate in rural areas - Beckmann, Markus; Garkisch, Michael; Zeyen, Anica (Journal of Small Business and Entrepreneurship, 2021)
Small and medium-sized enterprises (SMEs) play an important role for growth and sustainable development, particularly for rural areas in which MNCs are absent. Despite this link, there is little systematic research that investigates how SMEs address the particularities, opportunities, and challenges of rural areas based on their strengths and weaknesses. To fill this gap, this article uses a systematic literature review (SLR) that analyses 228 articles published between 2003 and October 2020. Our descriptive analysis shows that research on this topic has increased over time. Based on our thematic results, we juxtapose typical strengths and weaknesses of SMEs (enterprise perspective) and the opportunities and challenges of rural areas (spatial perspective). A key finding is that SMEs use relation-based collaboration as a meta-strategy to respond to these specific conditions. Wedding the theoretical perspectives of the RBV and transaction cost economics, we develop a conceptual model that explains why rural SMEs are in a particular need and position to use collaboration as a tool to innovate and access critical resources in otherwise resource-scarce rural areas. We then discuss how digitalization impacts our results regarding SMEs in rural space.
CRIS-Team Scopus Importer:2021-03-05
Keywords: collaboration; digitization; RBV; relationships; rural areas; SLR; Small and medium sized enterprises; SME; spatial context; systematic literature review; transaction costs